Epidemiological Features and Outcomes of HTLV-1 Carriers Diagnosed with Cancer: A Retrospective Cohort Study in an Endemic Country - Valcarcel, B (2023)
PURPOSEHuman T-lymphotropic virus type 1 (HTLV-1) is an endemic virus in Latin America that is directly linked to adult T-cell leukemia/lymphoma (ATL). Previous studies have suggested an oncogenic role of HTLV-1 in non-ATL neoplasms and have found higher mortality in HTLV-1 carriers without ATL.METHODSIn this retrospective cohort study, HTLV-1 carriers were identified through screening at a tertiary cancer center between 2006 and 2019. We compared the overall survival (OS) outcomes of patients with ATL with those with other solid or hematologic malignancies by sex stratification.RESULTSWe identified 1,934 HTLV-1 carriers diagnosed with cancer. The median age at diagnosis was 62 (range 20-114) years, 76% were female, 60% had no or elementary school education, and 50% were born in the Andean highlands. The most common non-ATL neoplasm was cervical cancer (50%) among females and non-ATL non-Hodgkin lymphoma (26%) among males. With a median follow-up of 66 months, the 5-year OS of HTLV-1 carriers with non-ATL neoplasms (26%-47% for females and 22%-34% for males) was inferior to those reported in the general population. As expected, patients with ATL had a worse prognosis (5-year OS: 10% for females and 8% for males).CONCLUSIONHTLV-1 carriers with cancer were middle age and from underprivileged settings, suggesting an undetected transmission among vulnerable populations, especially females. Survival estimates of HTLV-1 carriers with non-ATL neoplasms were lower than the regional outcomes. Future research should ascertain how the biology of HTLV-1 and health care disparities affect the outcomes of HTLV-1 carriers, as well as determine the burden of HTLV-1 infection in the cancer population to recommend screening in the outpatient setting of endemic regions. © American Society of Clinical Oncology.